2009
DOI: 10.1002/ptr.2977
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of the saponin fraction from Clematis chinensis Osbeck roots on osteoarthritis induced by monosodium iodoacetate through protecting articular cartilage

Abstract: The objective of the present study was to investigate the effect of the saponin fraction from Clematis chinensis Osbeck roots (SFC) on an osteoarthritis model in rats and to explore its underlying mechanisms. Osteoarthritis was induced by intraarticular injection of monosodium iodoacetate (MIA) into knee joints of rats, and SFC and diclofenac were orally administered once a day for 28 consecutive days. Joint swelling, macroscopic observation, histological assessment and proteoglycan (PG) degradation were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…Clinical (Blanco et al 1995;Greisbery et al 2002) and preclinical studies (Hashimoto et al 1998;Beltrán et al 2000) have indicated that NO level of osteoarthritis cartilages increased significantly in proportion with the number of apoptotic chondrocytes, demonstrating that NO is involved in the pathogenesis of osteoarthritis. Our previous study (Wu et al 2010) has demonstrated that SNP concentration-dependently led to a reduction of the viability of chondrocytes in parallel with an elevation of NO level, indicating that the chondrocyte impairment was NO-dependent. And in this study, it is observed that NO-induced death of chondrocytes was mainly by apoptosis, which was in accordance with previous reports (Hashimoto et al 1998;Beltrán et al 2000).…”
Section: Discussionmentioning
confidence: 92%
“…Clinical (Blanco et al 1995;Greisbery et al 2002) and preclinical studies (Hashimoto et al 1998;Beltrán et al 2000) have indicated that NO level of osteoarthritis cartilages increased significantly in proportion with the number of apoptotic chondrocytes, demonstrating that NO is involved in the pathogenesis of osteoarthritis. Our previous study (Wu et al 2010) has demonstrated that SNP concentration-dependently led to a reduction of the viability of chondrocytes in parallel with an elevation of NO level, indicating that the chondrocyte impairment was NO-dependent. And in this study, it is observed that NO-induced death of chondrocytes was mainly by apoptosis, which was in accordance with previous reports (Hashimoto et al 1998;Beltrán et al 2000).…”
Section: Discussionmentioning
confidence: 92%
“…According to the traditional Chinese medicinal view, the nature and flavor of Radix Clematidis are pungent, salty and warm, and channel tropism shows that Radix Clematidis acts on the urinary bladder meridian (State Pharmacopoeia Committee of People's Republic of China, 2010). Accumulative evidence has demonstrated that saponins extracted from Clematidis Radix possess anti-inflamatory (Fu et al, 2010;Shi et al, 2006) and chondroprotective (Hsieh et al, 2011;Wu et al, 2013Wu et al, , 2010 properties, and clematichinenoside AR (AR) has been isolated and identified as the major active component of triterpenoid saponins Ma et al,2009;Zhou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The chondroprotective efficacy of NSAIDs with inhibitory effects on MMPs still require verification from well-designed clinical trials, but these kinds of NSAIDs could be a better choice for patients with degenerative arthritis. In previous study, saponin fraction of Clematis chinensis was reported for its preventive effects on monosodium iodoacetate (MIA)-induced osteoarthritis (Wu et al, 2010). However, in our experiment, we used different arthritis inducers and quantitative tools to measure the anti-inflammatory arthritis effects of Clematis chinensis.…”
Section: Discussionmentioning
confidence: 96%